Ensino de relações número-quantidade para alunos da educação infantil - Vaz, Carolina (Universidade Federal de São Carlos, 2024)
Taking into account the uniqueness of students and the mathematical skills expected to be developed since early childhood education, the use of appropriate teaching procedures can contribute to the development of these skills and prevent gaps. The objective of the present study was to evaluate the effects of the teaching procedure, based on the stimulus equivalence paradigm, on learning relationships between number and quantity of children in early childhood education. Three students aged between 4 and 5 years old participated, enrolled in phase 5 of early childhood education at a municipal school in a medium-sized city in the interior of the State of São Paulo. A multiple probe design was used between groups of stimuli and also pre- and post-test assessment to separate quantity using manipulative material and an instrument to assess mathematical skills. The teaching procedure was divided into stages: familiarization with the participants; pre-test with manipulative material (selection of the number of items corresponding to the dictated number AD or the Arabic number BD); assessment of mathematical skills through the Mathematics Skills Registration and Assessment Protocol (PRAHM); evaluation of the relationships between dictated numeral and Arabic numeral (AC), between dictated numeral and quantity (AB), between Arabic numeral and quantity (BC) and between quantity and Arabic numeral (CB) through probes before and after each group of stimuli; teaching the conditional relationships between dictated numeral and Arabic numeral (AB) and between dictated numeral and amount (AC) for each group of stimuli and testing the emerging relationships between Arabic numeral and quantity (BC) and between quantity and Arabic numeral (CB) for each stimulus group; post-test with manipulable material. All teaching stages were conducted individually. The results showed that the three participants learned or maintained high performance in the relationships between dictated numerals, Arabic numerals and quantity, that is, the relationships between Arabic numerals and quantity (AB) and between quantity and Arabic numerals (AC) were taught or strengthened. and from them, the emergence of new relationships between Arabic numeral and quantity (BC) and between quantity and Arabic numeral (CB) was observed, or strengthened in the case of stimulus groups 1 and 2 for two participants. Furthermore, in the post-test, participants demonstrated improvement in their performance in selecting the quantity of manipulative materials in relation to the dictated number and the Arabic number. In general, the results demonstrated the contribution of the procedure to teaching relationships between number and quantity for early childhood education children.
Teaching number-quantity relationships to early childhood education students
Keywords: Ensino de matemática; Educação Infantil; Equivalência de estímulos; Teaching mathematics; Child education; Stimulus equivalence; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM